Power dissipation of a viscoelastic rolling wheel in finite deformations - Buezas, Fernando Salvador (2018)
A theoretical and numerical framework to evaluate rolling contact using a Lagrangian formulation in the sense of continuum mechanics is established. The treatment corresponds to a non-stationary and large deformation model that takes into account all inertial effects. A finite element formulation is implemented featuring cylinder- plate contact. The unilateral contact of hyperelastic and viscoelastic rolling wheel on a rough foundation on which friction laws hold is characterized by a highly nonlinear variational inequality. The solutions might predict the dependence of stress distribution with viscous properties. A parametric study shows the maximum power dissipation as a function of velocity, coefficient of friction and viscosity parameter.